2020
DOI: 10.1002/bab.2000
|View full text |Cite
|
Sign up to set email alerts
|

USP47 promotes apoptosis in rat myocardial cells after ischemia/reperfusion injury via NF‐κB activation

Abstract: An increasing number of studies have associated nuclear factor‐κB (NF‐κB) activation to the progression of myocardial infarction (MI). Multiple members of the ubiquitin‐specific protease (USP) family regulate the NF‐κB signaling pathway. This study attempted to investigate the function and underlying mechanism of USP family members in MI. Monocytes were isolated from peripheral blood samples of MI and healthy control, and the expression of several USP family members and NF‐κB was examined. After USP47 knockdow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Similarly, treatment Groups IV, V, and VI showed a well‐arranged sinusoid with hepatic venule groups, with disrupted hepatic venules, lack of a nucleus in hepatocytes revealing necrosis, infiltration of degenerated hepatocytes, and inflammation in Group III (Figure 6A). Fibrosis is the progression of the inflammation after the post‐MI 50 Groups I, V, and VI showed the lack of collagen accumulation. Group V showed mild thickening of the outer layer of epicardium ( tunica adventitia ), whereas Group VI showed inflammatory damage on the myocardial tissue ( tunica media ) with fibrosis (Figure 6B).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, treatment Groups IV, V, and VI showed a well‐arranged sinusoid with hepatic venule groups, with disrupted hepatic venules, lack of a nucleus in hepatocytes revealing necrosis, infiltration of degenerated hepatocytes, and inflammation in Group III (Figure 6A). Fibrosis is the progression of the inflammation after the post‐MI 50 Groups I, V, and VI showed the lack of collagen accumulation. Group V showed mild thickening of the outer layer of epicardium ( tunica adventitia ), whereas Group VI showed inflammatory damage on the myocardial tissue ( tunica media ) with fibrosis (Figure 6B).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, USP47 expression may be related to the progression of myocardial infarction. Downregulating USP47 reduced myocardial ischemia-reperfusion injury by inhibiting apoptosis (Hu et al, 2020).…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…At the post-transcriptional level, many non-coding RNAs are involved in regulating USP47 expression. USP47 is the target protein of miR-204-5p, and high miR-204-5p expression leads to down-regulation of USP47 expression, thereby inhibiting proliferation of gastric cancer and ovarian cancer cells (Zhang et al, 2015;Hu et al, 2020). USP47 is also a target protein of miR-188-5p in CRC.…”
Section: Post-transcriptional Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Ubiquitin (Ub)-specific proteases (UPSs), the largest subfamily of DUBs, remove Ub chains from the substrates to regulate the stability, activity and subcellular localization of the target substrates ( Lee et al, 2013 ; Eletr and Wilkinson, 2014 ). Increasing evidence has demonstrated that DUBs have a crucial role in cardiovascular diseases, such as cardiac hypertrophy, myocardial infarction, atrial fibrillation, heart failure, and others ( Liu et al, 2016 ; Bi et al, 2020a ; Bi et al, 2020b ; Hu et al, 2021 ). USP7 (also called Herpesvirus-associated ubiquitin-specific protease, HAUSP), the first identified DUBs, participated in cell proliferation, DNA damage response, tumourigenesis, inflammation, and apoptosis by regulating its substrates, such as MDM2/p53, PTEN, FOXO4, NF-κB, and other target proteins ( Khoronenkova et al, 2012 ; Smits and Freire, 2016 ; Xu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%